Batwoman. The third and final season [videorecording (DVD)] - Johnson, Camrus, 1994-; Skarsten, Rachel, 1985-; Tandy, Meagan, 1985-; Scott, Dougray, 1965- (Warner Bros., 2022)
In Season Three, Ryan Wilder must lead the Bat Team in stopping the next wave of villains created by the weapons lost in the Gotham River during the finale. And she'll have to do it with Alice by her side! As a new generation of Rogues torment Gotham, Batwoman and Alice must work together to stop them a predicament that threatens to upend the team's existing dynamics.